Caribbean generations : a CXC history source book - Gordon, Shirley C. (Trinidad : Longman Caribbean ; London ; New York : Longman Group, 1983)
Presents Caribbean area history, using original source material, in a format designed to aid students preparing for "O" level exams.
Includes bibliographical references (pages 310-328) and index.
NLJCols20082021
Keywords: Caribbean Area -- History -- Problems, exercises, etc; Caribbean Area -- History -- Sources; Caribbean Area -- History -- Problems, exercises, etc; Caribbean Area -- History -- Sources; Caribbean Area; Caribbean countries, to 1980 - Questions & answers - For Caribbean students; History; Problems and exercises; Sources